Analysis of Students’ Readiness to Prepare Research Reports in Research Methodology Courses - Netti Kariani Mendrofa; Ratna Natalia Mendrofa (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Students’ ability to prepare research reports is an important academic competence that must be developed as part of scientific literacy in higher education. A research report not only serves as the final product of learning in a research methodology course, but also reflects students’ readiness to understand research concepts, apply methodological procedures, and communicate research findings in a systematic and academically acceptable manner. In practice, students’ readiness to prepare research reports varies, even after they have completed a Research Methodology course. This study aimed to describe students’ readiness to prepare research reports in a Research Methodology course in terms of five aspects: methodological understanding, technical writing skills, academic readiness, psychological readiness, and learning support. This study employed a descriptive quantitative design involving 35 fifth-semester students in the Mathematics Education program. Data were collected using a four-point Likert-scale questionnaire consisting of 21 items, distributed online via Google Forms. Data were analyzed descriptively by calculating mean scores and categorizing students’ readiness levels. The results showed that, overall, students’ readiness was at a moderate level across all measured aspects. Learning support obtained the highest mean score, whereas technical skills for preparing research reports received the lowest. These findings indicate that strong learning support is not yet fully matched by students’ internal readiness. Therefore, this study recommends strengthening Research Methodology instruction by placing greater emphasis on research report writing practice, staged exercises, and continuous feedback.